Development of a Web-Based Medical Terminology Learning Application Integrating Medical Term Components and Definitions - Ayuk Era Edwina Noviana; I Made Sudarma Adiputra; Made Wahyu Aditya (Universitas Duta Bangsa Surakarta, 2026)
Background: Medical terminology is an essential competency for Medical Records and Health Information students because it supports accurate clinical documentation and diagnosis coding. However, students often experience difficulties in understanding medical terms and identifying their constituent elements, including prefixes, roots, and suffixes. Currently, few web-based medical terminology applications integrate medical term definitions together with prefix, root, suffix, and meaning information stored in a database into a single platform. This study aimed to develop a web-based medical terminology application as a learning medium. Methods: This study employed a Research and Development (R&D) approach using the Waterfall software development model. The application was developed using PHP and MySQL. User-entered medical terms were searched against a relational database containing predefined medical terms and prefix, root, suffix, and meaning information stored in the database. Matching records were retrieved and displayed, whereas unavailable terms generated search suggestions. The application was evaluated for functionality, interface design, and usability using black-box testing, interface design assessment, and the System Usability Scale (SUS) by two media experts and nine Medical Records and Health Information students. Results: The application achieved an average black-box testing score of 98%, indicating very valid functionality. Black-box testing confirmed that the application functioned as intended by retrieving and displaying predefined medical terminology records (e.g., bronchitis and rhinoplasty) together with the corresponding prefix, root, suffix, and meaning information stored in the database, while generating search suggestions for unavailable terms. The interface design assessment scored 96%, while the System Usability Scale achieved a score of 93, corresponding to Grade A+ with a Best Imaginable user experience. Conclusion: The developed application is feasible as a learning medium for medical terminology. The application assists users in understanding medical terms by displaying medical term definitions together with prefix, root, suffix, and meaning information stored in the database.